Psychometric Validation and Rasch Model Analysis of the Academic Resilience Scale for Indonesian University Students - Asradi Asradi; Freddi Sarman (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study addresses the limited availability of psychometrically validated instruments to measure academic resilience among Indonesian university students. The research aimed to develop and validate an Academic Resilience Scale using the Rasch model, which was chosen for its ability to provide linear and invariant measurement beyond Classical Test Theory. A total of 606 students from various universities participated. The 26-item scale was evaluated by experts and analyzed with Winsteps software. The findings demonstrated strong psychometric properties, with person reliability of 0.87, item reliability of 0.91, and Cronbach's alpha of 0.89, indicating high internal consistency. All items met validity criteria based on infit-outfit statistics (0.5 < MNSQ < 1.5). Unidimensionality was confirmed with 38.2% of raw variance explained by measures, exceeding the minimum threshold of 20%. Differential Item Functioning analysis revealed no gender bias across all items (p > 0.05). The Academic Resilience Scale exhibits robust psychometric characteristics and is a valid, reliable instrument for measuring academic resilience among Indonesian university students. The scale has practical implications for academic counseling, intervention design, and cross-cultural research in higher education settings. Keywords: academic resilience, psychometric validation, rasch model, higher education, indonesian university students